The Reliance Damages for Depending Upon the Contract - An Analytical Comparative Study with the Iraqi Civil Law - Ali, Yunus (Journal of Legal Sciences, 2023)
The reliance damages for depending upon the contract are considered as a type of damages arising from the breach of the contract, which are included within the common law remedies for the damage and loss suffered by the non-breaching party. It is worth-bearing in mind that the reliance damages are monetary in nature, and different from such equitable remedies as the specific performance and the injunction which are of real nature. It is to be noted that this piece of research is dedicated to study the concept of the reliance damages in the English law, as well as their states, the judicial doctrines upon which this type of damages is based, and the manner how the courts estimate them. Compared with situation of the Iraqi civil law No. (40) of 1951, which adopts the concept of the damages to compensate the loss suffered or sustained and the lost profit anticipated. It is to be noted also that the problem of the study lies in studying this type of damages, which is not regulated by the Iraqi civil law, particularly the pre-contractual reliance damages. and an attempt to suggest some relevant recommendations to the Iraqi legislator to treat the insufficiency due to the non-regulation of this type of damages. As well as suggesting a legal regulation to them.